IT Quality and Organizational Development – using Action Research to promote Employee Engagement, Leadership development, Learning and Organizational Improvement - Henriques, T.; O'Neill, Henrique (British Academy of Management, 2014)
Quality is often reduced to visions strongly shaped by operational and tactical instruments – relegating crucial Organizational Development (OD) aspects, which sustain Learning and Innovation, to a minor dimension. This is a quite common situation in the IT areas. The Program described in this paper was developed within a Bank’s IT Division aiming to induce organizational transformation and to produce strategic action and behavioural changes, leading to an effective improvement on Customers and Employees’ Satisfaction. A first Organizational Development cycle was focused on Service Culture, Leadership, and Employee Engagement and has developed the conditions for a second cycle, based on the acquired knowledge and on its emergent strategic decisions (double loop), being thus devoted to action implementation. The Program has followed an Action Research paradigm – addressing a complex, transformational, planed change, and using a multidimensional, integrative approach, based on a holistic and open systemic view. It was not target for rising or testing new theories, but, mainly, to seek the fulfilment of existing empirical and methodological gaps. Although its achievements cannot be generalized outside the context, they can be transposed to other settings, thus revealing important Management Implications. They shape the relevance basis for this article: a key contribution on a holistic, values-based, and participative framework to address organizational transformation, and the associated critical success factors.